2018
DOI: 10.18512/1980-6477/rbms.v17n1p91-100
|View full text |Cite
|
Sign up to set email alerts
|

Limites Críticos De Ndvi Para Estimativa Do Potencial Produtivo Do Milho

Abstract: RESUMO - A estimativa do potencial produtivo da cultura do milho ao longo do ciclo de desenvolvimento é uma das novas práticas agrícolas que vêm sendo utilizadas para qualificar o manejo da cultura. Neste sentido, destaca-se a inserção de sensores de vegetação, com a finalidade de realizar o monitoramento do desenvolvimento e da condição nutricional da cultura ao longo do seu ciclo. O objetivo do presente trabalho foi determinar os limites críticos do Índice de vegetação por diferença normalizada (NDVI) para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
7
0
3
Order By: Relevance
“…Among the relationships between VIs and the N content absorbed by the plant at the V7 growth stages of the corn crop (Figure 5), V11 (Figure 6) and V12 (Figure 7), the ones that showed the best relationships were those in the V12 stage. For the V7 stage, the indices EVI2 and GNDVI (RPAS platform) showed the best relations, with CARVALHO, L. F. D. et al The use of IVs, in the different platforms is an alternative for real-time assessments of the nutritional status of crops and can be an important tool in determining nitrogen fertilizer doses more consistent with the real need for N by plants (VIAN et al, 2018). Schmidt et al (2011) found a satisfactory relationship between the NDVI readings and the nitrogen fertilizer dose demand for corn.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Among the relationships between VIs and the N content absorbed by the plant at the V7 growth stages of the corn crop (Figure 5), V11 (Figure 6) and V12 (Figure 7), the ones that showed the best relationships were those in the V12 stage. For the V7 stage, the indices EVI2 and GNDVI (RPAS platform) showed the best relations, with CARVALHO, L. F. D. et al The use of IVs, in the different platforms is an alternative for real-time assessments of the nutritional status of crops and can be an important tool in determining nitrogen fertilizer doses more consistent with the real need for N by plants (VIAN et al, 2018). Schmidt et al (2011) found a satisfactory relationship between the NDVI readings and the nitrogen fertilizer dose demand for corn.…”
Section: Resultsmentioning
confidence: 98%
“…The use of the IV tool allows the real-time and in-situ estimation of the nutritional status of the plants in different growth stages and also the productive potential of the corn crop, allowing the nitrogen fertilization to be adjusted and applied according to the development of the crop (LI et al, 2010;VIAN et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os IVs foram calculados com o auxílio do software geoestatístico em plataforma livre QGIS sendo utilizado a Calculadora Raster, algoritmo com a capacidade de realizar os cálculos referentes às expressões matemáticas de cada índice de vegetação (IV), sendo estes: IV por diferença normalizada (NDVI), Vian et al (2018), Equação (1); IV por diferença normalizada da borda vermelha (NDRE), Fitzgerald et al (2006) Equação (2). NDVI = (Nir -Red) / (Nir+Red) (1) NDRE = (Nir-Red Edge) / (Nir + Red Edge)…”
Section: Materiais E Métodosunclassified
“…The technological advances of RPAs have been remarkable in recent years, both for applications relating to land use, as in issues inherent in the reduction of environmental damage, reducing the need for inputs and maximizing profits (Honda;Jorge, 2013). An increasingly efficient application of N during the crop cycle is also being pursued, since this nutrient promotes the development of the plant, while a low availability of this nutrient prevents higher yields in maize (Vian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%